Lebanon Economic Monitor, Fall 2019 : So When Gravity Beckons, the Poor Don't Fall - World Bank (World Bank, Washington, DC, 2020)
Lebanon is in Crisis. While it is too early to gauge the economic impact of recent events, it is important to note that even prior to the eruption of the demonstrations, the World Bank projected a small recession in 2019; we now estimate that the recession will be deeper. There has been an unprecedented banking holiday, with banks closed over October 18-31 for retail and other transactions, reopening thereafter with informal capital controls and other uncoordinated measures, then closing again for 10 days on November 9. Critical short-term financing for businesses has been interrupted, leading to disruptions all along the supply chain and an ultimate impact on workers. Unemployment is expected to rise and poverty, already high, will follow. The emerging parallel exchange market is likely to trigger inflationary pressures, hurting the poor and middle class disproportionally. Shortages of imports are also expected to materialize. The crisis is a culmination of chronic conditions that have long impeded Lebanon’s development process. Lebanon’s Systematic Country Diagnostic (SCD)1 identified elite capture, hidden behind the veil of confessionalism and confessional governance, as one of two overarching constraints for the country’s economic development (the other being conflict and violence, stemming, in part, from the broader dynamics of conflict in the Middle East). Under the guise of preserving post-war confessional balances, a postwar elite emerged to command the main economic resources, both private and public, generating large rents and dividing the spoils of uncompetitive markets and a dysfunctional and hallowed state.